2019
DOI: 10.1002/pd.5540
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal MRI findings in open spinal dysraphism following intrauterine repair via open versus fetoscopic surgical techniques

Abstract: Purpose The purpose of the study is to examine MRI findings of the brain and spine on prenatal and postnatal MRI following intrauterine repair of open spinal dysraphism (OSD) by open hysterotomy and fetoscopic approaches. Materials and methods This study is a single‐center HIPAA‐compliant and IRB‐approved retrospective analysis of fetal MRIs with open spinal dysraphism from January 2011 through December 2018 that underwent subsequent prenatal repair of OSD. Results Sixty‐two patients met inclusion criteria: 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Most authors suggest that closure of the defect promotes reversal of cerebellar herniation which reopens the communication between the fourth ventricle and subarachnoid space [ 37 , 42 , 44 , 45 ]. The pathogenesis of hydrocephalus in OSB is however likely multifactorial and other authors have postulated that impaired absorption of CSF back into the venous system (communicating hydrocephalus) is a contributory factor.…”
Section: Resultsmentioning
confidence: 99%
“…Most authors suggest that closure of the defect promotes reversal of cerebellar herniation which reopens the communication between the fourth ventricle and subarachnoid space [ 37 , 42 , 44 , 45 ]. The pathogenesis of hydrocephalus in OSB is however likely multifactorial and other authors have postulated that impaired absorption of CSF back into the venous system (communicating hydrocephalus) is a contributory factor.…”
Section: Resultsmentioning
confidence: 99%
“…13 On prenatal MRI, the most caudal spinal hyperintense disc space was considered as the 5th lumbar vertebra-1st sacral vertebra, 14 and the lowest horizontal vertebral body was considered as the 5th lumbar vertebra. 15 Alternatively, the last ribbearing vertebra was identified to determine the 12th thoracic vertebral level. On postnatal imaging, the odontoid was labeled as the 2nd cervical vertebral level.…”
Section: Standard Diagnosis Of Congenital Malformations In the Spine ...mentioning
confidence: 99%
“…It provides a detailed assessment of the fetal spine and brain and also helps to rule out other associated anomalies. The presence or absence of an MMC sac, the size of the sac (when present), and size of the vertebral arch defect are all relevant spine MRI parameters; the presence or absence of hindbrain herniation, degree of hindbrain herniation (when present), and ventricular size are important brain MRI parameters 168. These findings are all of prognostic significance as they guide the approach to management.…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%
“…Early MMC closure restores hindbrain herniation, which has been associated with a lower risk of hydrocephalus when compared with postnatal MMC closure 163. Small series have shown that in utero MMC closure improves hindbrain herniation prenatally, as early as 4-6 weeks postoperatively 168186…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%